Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Moderasi Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pasaman - Adek Tamara; Heliyani (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
This research aims to analyze the influence of workload and work stress on employee performance with job satisfaction as a moderating variable at the Pasaman Regency Population and Civil Registration Service. This research is motivated by the existing problems of Workload and Job Stress which influence job satisfaction which also has an impact on employee performance at the Pasaman Regency Population and Civil Registration Service. The research uses a quantitative approach with the Partial Least Square method with Structural Equation Modeling. Data collection techniques using questionnaires and observation. The respondents of this study were 55 employees of the Population and Civil Registration Service of Pasaman Regency. Samples were drawn using the total sampling method where the entire population in this study was used as the research sample. Data processing and hypothesis testing were calculated using the SmartPLS program. The research results show that workload and work stress variables have a significant effect on employee performance. Job satisfaction cannot moderate the relationship between workload variables and employee performance. Job satisfaction cannot moderate the relationship between work stress variables and employee performance. This means that job satisfaction cannot strengthen or weaken the influence of workload on employee performance and job satisfaction cannot strengthen or weaken the influence of work stress on the performance of Pasaman Regency Population and Civil Registration Service employees.